2015
DOI: 10.1007/82_2015_5017
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Immune Evasion Proteins: Structure, Function, and Host Adaptation

Abstract: Staphylococcus aureus is a successful human and animal pathogen. Its pathogenicity is linked to its ability to secrete a large amount of virulence factors. These secreted proteins interfere with many critical components of the immune system, both innate and adaptive, and hamper proper immune functioning. In recent years, numerous studies have been conducted in order to understand the molecular mechanism underlying the interaction of evasion molecules with the host immune system. Structural studies have fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 266 publications
1
70
0
2
Order By: Relevance
“…The triple-helix motif is a thermodynamically stable structure which can accommodate high sequence diversity and adapt to binding a wide variety of targets (28). However, this simple structural motif is typically modified by an N-terminal extension that imparts specific function to the protein in question (27).…”
Section: Discussionmentioning
confidence: 99%
“…The triple-helix motif is a thermodynamically stable structure which can accommodate high sequence diversity and adapt to binding a wide variety of targets (28). However, this simple structural motif is typically modified by an N-terminal extension that imparts specific function to the protein in question (27).…”
Section: Discussionmentioning
confidence: 99%
“…We should keep in mind, however, that inducing overexpression of a virulence trait is artificial and does not resemble the natural situation. Human S. aureus strains are highly adapted to the human system and are not capable to easily establish infection in mice, which can partly be explained by the human specificity of many virulence factors [5] , but might also be related to differential expression of virulence determinants in humans and mice. With the current lack of more suitable in vivo models, the development of this SSL3-overproducing S. aureus strain provided a valuable tool to study the effect of SSL3 in a mouse model in vivo enabling us to determine its relative contribution to bacterial virulence.…”
Section: Discussionmentioning
confidence: 99%
“…It secretes two small proteins that potently interfere with TLR2 signaling: staphylococcal superantigen-like protein 3 (SSL3) and 4 (SSL4) [17] . SSL3 and SSL4 are part of a larger, structurally related family of staphylococcal proteins that have diverse functions but are all involved in immune modulation [5] . SSL3 is the more potent inhibitor of the two, and the crystal structure of the complex of SSL3 and TLR2 revealed that SSL3 inhibits TLR2 through interfering with both lipopeptide binding and dimerization [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of S. aureus is linked to its ability to express a vast array of virulence genes to allow adaption to host immune systems and survival in challenging microenvironments. 1 Although mammals have developed both innate and adaptive immune strategies to fight invasive microbes, S. aureus has coevolved with these host defense systems and secretes a variety of immune evasion determinants including staphylococcal super-antigen-like proteins to manipulate host immune responses. 2 The expression of a large number of virulence factors is coordinately regulated during pathogenesis and requires both two-component regulatory systems and members of the SarA protein family, comprising an interdependent and tightly controlled network.…”
mentioning
confidence: 99%